Ahmad al-Mansur the beginnings of modern morocco - Garcia-Arenal, Mercedes (Oxford One World Publications, 2009)
Sultan Ahmad al-Mansur (1578-1603) was one of the most significant rulers in the history of Morocco, which to this day bears the mark of his twenty-five year rule in the sixteenth century. A brilliant political and military tactician, cunning diplomat and descendent of the Prophet Muhammad himself, al-Mansur was a charismatic religious authority with ambitions to become Caliph and ruler of all Islam. Spanning four continents, this lucid introduction assesses this fascinating figure and his legacy amidst the political intrigue, colonial discovery, and military conquest that dominated the age. Mercedes Garca̕-Arenal is Professor of Arabic Studies at the Higher Council of Scientific Research in Madrid.
Includes index
Keywords: Ahmad al-Mansur